Update on Janus Kinase Antagonists in Inflammatory Bowel Disease - Boland, Brigid S. (2014)
Janus kinase (JAK) inhibitors have emerged as a novel orally administered small molecule therapy for the treatment of ulcerative colitis and possibly Crohn’s disease. These molecules are designed to selectively target the activity of specific JAKs and offer a targeted mechanism of action without risk of immunogenicity. Based on data from clinical trials in rheumatoid arthritis and phase 2 studies in inflammatory bowel disease, tofacitinib and other JAK inhibitors are likely to become a new form of medical therapy for the treatment of inflammatory bowel disease.